The STRATEGI PEMBELAJARAN KOLABORATIF UNTUK MENINGKATKAN HASIL BELAJAR DALAM PENDIDIKAN AGAMA KRISTEN - Manurung, Ribka Ekaristy; Nauli, Jhonnedy K. (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2024)
This study is motivated by the low active engagement and learning outcomes of students in Christian Religious Education (CRE) due to the use of conventional teaching methods, which tend to be passive. The aim of this study is to analyze collaborative learning strategies as an alternative to improving students' learning outcomes, particularly in understanding the teachings of Jesus Christ. This research employs a literature review method. Data were collected from scholarly journals, academic books, and other relevant documents, and analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that collaborative learning enhances students' understanding of the teachings of Jesus Christ, strengthens social skills such as teamwork and empathy, and creates a more interactive learning environment. This strategy is effective in integrating collective reflection and group discussion, enabling students to explore the meaning of religious teachings more deeply.